COMMUNITY UNDERSTANDING OF SIDODADI VILLAGE AND DURIAN NINE VILLAGE ON SUMATRA ELEPHANT CONSERVATION (ELEPHAS MAXIMUS sUMATRANUS, Temminck) - Helida, Asvic; Hidayat, Yayat; Pamungkas, Laksono; syachroni, sasua hustati (Sylva Jurnal Ilmu-ilmu Kehutanan, 2022)
The forest has a function as a place for various animals in it, such as the Sumatran Elephant (Elephas maximus sumatranus. Temminck). The condition of elephant habitat is decreasing in Sumatra, especially in South Sumatra Province. The decline in the quality of elephant habitat in South Sumatra Province has resulted in an increasingly narrow shortage, one of the conservation areas for elephant habitat protection, namely the Gunung Raya Wildlife Reserve. The research method uses a quantitative descriptive approach. Descriptive research is conducted to describe a symptom or event that occurs factually, systematically and accurately. The sampling method uses the Simple Random Sampling Technique, namely the sampling technique from the population is carried out randomly without regard to the strata in that population. Methods of data management using quantitative descriptive analysis using Likert Scale analysis. The results showed that the assessment of community understanding was 86.20%, this indicated that the people of Sidodadi Village and Durian Sembilan Village knew about the existence of Gunung Raya Wildlife Sanctuary, while the level of public attention to environmental and forestry issues was 65.51% of the people did not know or lacked attention to environmental problems, and Agencies responsible for solving environmental and forestry problems amounting to 68.98%, this is based on community statements that the village head is responsible for solving environmental and forestry problems.